Penalaran Proporsional dalam Pendidikan Matematika: Tinjauan Literatur Sistematis (SLR) - Prismadian Amalia Putri; Agus Susanta; Nurul Astuty Yensy (FKIP Universitas Mataram, 2025)
This systematic literature review analyzes international evidence on proportional reasoning (PR) in K–12 education and teacher training. We synthesized eight studies and identified four key patterns. Contexts with hands-on activities help students transition from intuitive to formal strategies. Students often succeed with probability ratios, but struggle with visual biases. Example-based practice with self-explanation improves probabilistic reasoning, especially for less prepared students. Finally, diagnostic tools such as construct maps are useful for tracking student progress from